2008
DOI: 10.1016/j.cellbi.2007.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Plant tubulin intronics

Abstract: Introns of plant tubulin genes are useful molecular tools to study IME (Intron Mediated Enhancement of gene expression) and to define plant genetic and evolutionary relationships through ILP (Intron Length Polymorphism). Here we show that the intron present within the 5'UTR sequence of some rice beta-tubulin genes can sustain IME in rice transgenic plants and that degenerated oligonucleotide mixtures designed to amplify the first and the second intron present within the coding sequence of plant beta-tubulin ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Whether the prediction of pre‐miRNA in HpAOX1b and the suggestion that polymorphisms can interfere with miRNA synthesis in intron 1 have practical impact need to be validated by ‘wet’ experimentation. Validation would give support to the current view that 5′ located introns should be more important for gene regulation than introns more directed to the 3′end of the gene (Breviario et al 2008, Rose et al 2008, Rudd et al 2004, Tetko et al 2006).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Whether the prediction of pre‐miRNA in HpAOX1b and the suggestion that polymorphisms can interfere with miRNA synthesis in intron 1 have practical impact need to be validated by ‘wet’ experimentation. Validation would give support to the current view that 5′ located introns should be more important for gene regulation than introns more directed to the 3′end of the gene (Breviario et al 2008, Rose et al 2008, Rudd et al 2004, Tetko et al 2006).…”
Section: Discussionmentioning
confidence: 68%
“…Introns can affect either the level or the site of gene expression through intron‐mediated enhancement of gene expression and intron‐dependent spatial expression, respectively. It is often observed that introns that are most proximal to the 5′ end of a gene are the ones that exert a more pronounced effect on gene expression (Breviario et al 2008, Rose et al 2008). Chromosomal structures and chromatin modeling supporting transcription and recombination activities can also rely on motifs located in introns, such as scaffold or matrix attachment regions (S/MARs) (Shaposhnikov et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Gene organization and expression of main cytoskeletal proteins represent strong interest from opening possibilities to use this knowledge for different molecular genetic purposes. For example, length polymorphism of tubulin gene introns is proposed even to assess genetic diversity in plant species (Bardini et al, ; Breviario et al, ; Gavazzi et al, ). Rabokon et al () used this approach to differentiate between the accessions of Aegilops biuncialis Vis., a wild relative of wheat.…”
Section: Gene Organization and Expressionmentioning
confidence: 99%
“…In the case that the number of generated molecular markers is too low, the TBP -2nd intron approach can be used as an additional source of molecular variation. This kind of combinatorial TBP (cTBP) was validated analysing nine cultivars of oilseed rape and subsequently used to assess species/varieties relationships in Eleusine and Arachis, nine species each (Breviario et al, 2007) and in common bean (Breviario, Gianì, Ponzoni, Mastromauro, & Morello, 2008).…”
Section: Introductionmentioning
confidence: 99%